From Perceived Economic Inequality to Support for Redistribution: The Role of Meritocracy Perception - Lope Tejero-Peregrina; Guillermo Willis; Ángel Sánchez-Rodríguez; Rosa Rodríguez-Bailón (International Review of Social Psychology)
Economic inequality negatively impacts the welfare in our societies, yet there is reluctance to support measures aimed at alleviating its effects. To enhance our comprehension of how inequality influences support for redistribution, this paper investigates the mediating role of descriptive meritocracy (i.e., the degree to which meritocracy is perceived to exist in society). Using a cross-sectional study (N = 1536) and a follow-up experimental-causal-chain design in two subsequent experiments (N = 530), we show that the perception of inequality leads to the perception that society is not meritocratic, which, in turn, promotes support for redistribution. These results underscore the significance of perceiving economic inequality in order to dismantle the normative meritocratic narratives that hinder its reduction. We discuss these findings as part of the effects of economic inequality on the normative climate that influences our individual outcomes.